Crime Rates in Developed Western Countries The Effect of Safety Approach in Falling - Kizmaz, Zahir (Ilem, 2022)
This article focuses on the effect of opportunity theories and the security thesis associated with these theories on the decrease in crime rates observed in many developed countries. In the study, firstly, some important factors that are assumed to be effective in the decrease in crime rates are discussed. In this context, the decrease in crime in developed countries is mainly explained by many factors or approaches such as decreased drug use, lega-lization of abortion, increased police visibility, development of new policing models, increased incarceration rates, changes in gun policies, changes in population structure and economic improvements. It has been argued that many of these factors, or approaches to these factors, may be partially successful in explaining crime decreases and are more appropriate to explain crime decreases in the United States in particular. In this context, the importance and impact of the explanation potential of the security thesis as a more general explanation framework including the declines in European countries will be pointed out. The security hypothesis or approach explains the reason for the decrease in crime rates through the development and implementation of improved and enhanced security measures aimed at eliminating crime opportunities. Within the scope of the security thesis, the effect of proactive policing models on the drops of crime rates was also emphasized.
Keywords: Decline in crime rates; crime drop; security thesis; theories of opportunity; developed countries